2015
DOI: 10.4236/aim.2015.52011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sowing Season and Host Crop Identity on the Community Structure of Arbuscular Mycorrhizal Fungi Colonizing Roots of Two Different Gramineous and Leguminous Crop Species

Abstract: Introduction of cover crops may improve the diversity of arbuscular mycorrhizal fungi (AMF) in roots and soil under crop rotational systems; therefore, it is necessary to determine the potential for AMF communities to improve sustainable food production. We investigated the impact of cover crops, including wheat (Triticum aestivum L.), barley (Hordeum vulgare L.), pea (Pisum sativum L.), and hairy vetch (Vicia villosa Roth.), on the AMF communities in their roots in autumn and spring sowing seasons with PCR-DG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
1
14
1
Order By: Relevance
“…This could be one reason why P fertilizer input did not change the diversity of the AMF communities in tomato plants. Additionally, the impact of soil P on the diversity of AMF communities still remains a controversial subject, and the results could be related to P application rates [80], sampling times [83], host plant species [84,85], and agricultural management [86][87][88][89][90]. Our results were inconsistent regarding P fertilization on the diversity of AMF communities compared to previous reports.…”
Section: Effect Of P Fertilizer Level On the Amf Communities In Tomatcontrasting
confidence: 82%
“…This could be one reason why P fertilizer input did not change the diversity of the AMF communities in tomato plants. Additionally, the impact of soil P on the diversity of AMF communities still remains a controversial subject, and the results could be related to P application rates [80], sampling times [83], host plant species [84,85], and agricultural management [86][87][88][89][90]. Our results were inconsistent regarding P fertilization on the diversity of AMF communities compared to previous reports.…”
Section: Effect Of P Fertilizer Level On the Amf Communities In Tomatcontrasting
confidence: 82%
“…However, U. humidicola presented similar mycorrhizal colonization to monocropped and intercropped maize. Host preference of AMF has been described for annual and perennial herbaceous species [51], especially related with cultivated species [52]. Higher root colonization on maize than verified in the present study, ranging from 60 to 80%, was observed by GarcĂĄ-GonzĂĄles et al [53], influenced by barley (Hordeum vulgare L.. cv.…”
Section: Mycorrhizal Measurementssupporting
confidence: 66%
“…Finally, we remark the different pattern for barley and vetch in both sunflower and maize crops in which the benefits to barley on AMF were larger compared to vetch. Higo et al (2015) compared in a pot experiment the performance of four potential CCs (two legumes and two grasses) and found higher values of AMF colonization in the roots of barley compared with hairy vetch. They attributed these differences to host selectivity.…”
Section: Discussionmentioning
confidence: 99%